E-182 A multicentric experience for the use of flow diverter in the treatment of anterior communicating artery aneurysms. (23rd July 2022) - Benalia, V; Cortez, G; Koçer, N; Islak, C; Saatci, I; Cekirge, S; Baltacıoğlu, F; Dabus, G; Mounayer, C; Siddiqui, A; Lopes, D; Brinjikji, W; et al.
Abstract : Introduction: The anterior communicating artery (AcomA) is among the most common site of intracranial aneurysms. AcomA aneurysms are at increased risk of rupture when compared to other locations. Due to morphological particularities in this region, different technical challenges may arise for the mainstream treatments. We aim to report the experience of flow diverters (FDs) as an emerging strategy for treating AcomA aneurysms. Methods: This is a retrospective, self-adjudicated, multicentric experience from 7 centers across three countries (United States, France, and Turkey). Inclusion criteria encompassed patients with AcomA treated with FDs between January 2012 and December 2021. Outcomes of interest included aneurysm occlusion, complications, and functional outcomes. Complete occlusion was defined as O'Kelly-Marotta class D (OKM-D). Clinical outcomes were assessed using the modified Rankin Scale (mRS) at discharge and last follow-up. Postoperative complications included hemorrhage, parent vessel occlusion, ischemic events, intra-stent thrombosis, and intra-stent stenosis. Mortality rates were based on the last follow-up. Statistical analysis was performed using R (R Foundation for Statistical Computing, Vienna, Austria). Results: One-hundred and eighty-two patients harboring 183 AcomA treated with FDs met inclusion criteria. Mean age was 58.8±12.7, and the majority of patients were female (105/182, 56.1%). Most aneurysms were unruptured (143/183, 76.5%), and the most common location was on the AcomA itself (110/183, 58.9%), followed by A1-A2 junction with the involvement of the AcomA (45/183, 24.1%). In half of the patients, both anterior cerebral arteries had similar sizes (48.1%). A variable pattern of aneurysm filling was noted, with the majority filling from one side only (23.5%). The most common morphology was saccular (169/183, 90.4%), with a branch involvement in 27.3% of cases. The mean vessel diameter was 2.37mm (SD 0.41mm, range 2.1–2.7mm), whereas the mean neck size was 3.77mm (SD 1.69mm, range 2.7–4.7mm). Mean follow-up time was 17.2 months (SD 11.5, range 6.5–25), with a complete occlusion rate of 83.4%. Favorable functional (mRS 0–2) outcome at the last follow-up was reported at 96.8%. Univariate analysis demonstrated that smoking, aneurysm located in Acom proper artery, and previously ruptured aneurysm were more likely to have a complete occlusion in late follow-up. The mortality rate was 1.6% (3/182), where two cases were adjudicated as procedure-related. In one case, acute postoperative occlusion of the left A1 and supraclinoid internal carotid artery led to a high stroke burden, despite successful thrombectomy. A second patient developed an extensive intraparenchymal hemorrhage. The last patient presented with a ruptured aneurysm with worsening vasospasm and delayed cerebral ischemia despite adequate management and aneurysm securing. Conclusion: Flow diverters appear to be a safe and effective treatment for anterior communicating artery aneurysms, presenting as an alternative strategy in the armamentarium of interventionalist. Mid-term results were favorable, and complication rates were low. Additional studies with longer follow-up time and independent adjudication are warranted to confirm the safety and effectiveness of the technique. Disclosures: V. Benalia: None. G. Cortez: None. N. Koçer: None. C. Islak: None. I. Saatci: None. S. Cekirge: None. F. Baltacıoğlu: None. G. Dabus: None. C. Mounayer: None. A. Siddiqui: None. D. Lopes: None. W. Brinjikji: None. A. Aghaebrahim: None. E. Sauvageau: None. R. Hanel: 1; C; Unrestricted research grant from NIH, Interline Endowment, Microvention, Stryker, CNX.. 2; C; Medtronic, Stryker, Cerenovous, Microvention, Balt, Phenox, Rapid Medical, and Q'Apel. He is on advisory board for MiVI, eLum, Three Rivers, Shape Medical and Corindus.. 4; C; InNeuroCo, Cerebrotech, eLum, Endostream, Three Rivers Medical Inc, Scientia, RisT, BlinkTBI, and Corindus.